The Bourne identity - Liman, Doug.; Crowley, Patrick Timothy; Gladstein, Richard N.; Gilroy, Tony.; Herron, William Blake; Damon, Matt.; Potente, Franka, 1974-; Cooper, Chris, 1951-; Owen, Clive; Cox, Brian, 1946-; Akinnuoye-Agbaje, Adewale, 1967-; Wood, Oliver; et al. (Universal City, CA : Universal Pictures, 2002)
Bourne, is pulled from the sea suffering from amnesia with a pair of bullet wounds in his back. His only clue to his own identity is a bank account number etched on a capsule implanted in his body. He finds the Zurich bank where money, a gun, and several passports with different names await. He quickly realizes he can trust no one and offers a German gypsy named Maria ten thousand dollars for a ride to Paris. With Maria's reluctant help, Bourne edges closer to the truth, something CIA officials want concealed at all costs.
Originally produced as a motion picture in 2002.
Based on the novel by Robert Ludlum.
Director of photography, Oliver Wood ; editor, Saar Klein ; music, John Powell ; costume designer, Pierre-Yves Gayraud ; production designer, Dan Weil.
Matt Damon, Franka Potente, Chris Cooper, Clive Owen, Brian Cox, Adewale Akinnuoye-Agbaje.
MPAA rating: PG-13, for violence and some language.
VHS ; stereo.
Keywords: Carlos, -- the Jackal -- Drama; United States. -- Central Intelligence Agency -- Drama; Undercover operations -- Drama; Terrorists -- Drama; Amnesia -- Drama; Assassins -- Drama; Intelligence officers -- Drama; Bourne, Jason (Fictitious character) -- Drama; Video recordings for the hearing impaired; Feature films; Spy films; Adventure films; Videocassettes